A Novel Minutiae Triangulation Technique for Non-invertible Fingerprint Template Generation. (30th December 2021) - Trivedi, Amit Kumar; Thounaojam, Dalton Meitei; Pal, Shyamosree
Abstract: The fingerprint is the readily available and most widely used biometrics for the security of a system. In order to impart the security of the template database, it is important to make the fingerprint template robust to fingerprint reconstruction, i.e., invertibility. In this paper, a fingerprint template is proposed using a novel minutiae triangulation technique. In this triangulation technique, the set of minutiae of a template is taken to generate a set of minutiae triplets each forming a triangle. After this, a minutiae transformation is applied to obtain a set of triplets of internal angles of the triangle which also removes the minutiae location and orientation information. In the absence of this information, the orientation map of the fingerprint cannot be estimated. This set of triplets together with some other information is used as a proposed fingerprint template. The proposed system is experimented using standard FVC2000, FVC2004 and FVC2006 databases and yields better results in terms of EER (Equal Error Rate) as compared with the state-of-art techniques. Highlights: A novel minutiae triangulation technique for generating a robust fingerprint template is proposed. The proposed threshold for minutiae triplet validation is adaptive. The proposed fingerprint template is robust against fingerprint deformation.